2012
DOI: 10.1093/nar/gks756
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the biocompatibility of click-linked DNA in Escherichia coli

Abstract: The biocompatibility of a triazole mimic of the DNA phosphodiester linkage in Escherichia coli has been evaluated. The requirement for selective pressure on the click-containing gene was probed via a plasmid containing click DNA backbone linkages in each strand of the gene encoding the fluorescent protein mCherry. The effect of proximity of the click linkers on their biocompatibility was also probed by placing two click DNA linkers 4-bp apart at the region encoding the fluorophore of the fluorescent protein. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…More recently the chemical diversification of nucleic acids has been attempted in vivo to propagate additional types of nucleic acids (XNA) as templates for DNA synthesis in E. coli and for transcription into RNA in mammalian cells . In addition, DNA with a triazole linker instead of a phosphodiester bound have been accepted by E. coli , and human cells. It has also been reported that a semisynthetic organism is able to replicate with a single unnatural base pair in vivo .…”
Section: Figurementioning
confidence: 99%
“…More recently the chemical diversification of nucleic acids has been attempted in vivo to propagate additional types of nucleic acids (XNA) as templates for DNA synthesis in E. coli and for transcription into RNA in mammalian cells . In addition, DNA with a triazole linker instead of a phosphodiester bound have been accepted by E. coli , and human cells. It has also been reported that a semisynthetic organism is able to replicate with a single unnatural base pair in vivo .…”
Section: Figurementioning
confidence: 99%
“…Recent reports from Brown, El-Sagheer and Tavassolli have demonstrated that oligonucleotides containing a triazole linkage in place of a phosphodiester are competent substrates for PCR and thus could provide a “readable” encoding sequence 16 17 18 19 . Based on these results, and our prior experience with Cu-catalyzed alkyne-azide cycloaddition (CuAAC) of oligos 20 , we wondered whether a readable chemical ligation strategy might offer some advantages over the current enzymatic methods.…”
mentioning
confidence: 99%
“…However, there possibility that the success of these experiments was a consequence of selective pressure on the essential antibiotic resistant clickcontaining gene. To resolve this we repeated the work with a plasmid containing click DNA backbone linkages in the gene encoding the fluorescent protein mCherry which is clearly not required for survival of the bacteria (Sanzone et al 2012). The effect of the proximity of the click linkers on biocompatibility was also probed by placing two click DNA linkers 4-bp apart in the region encoding the mCherry fluorophore.…”
Section: In Vivo Biocompatibility Of the Triazole Linkagementioning
confidence: 99%